Towards a nuclear weapon-free and non-violent world (Vikas, 1990)
The problem is that once you have gotten your nifty new product, the Towards A Nuclear Weapon Free And Non Violent World gets a brief glance, maybe a once over, but it often tends to get discarded or lost with the original packaging.